Linkage group assignments for two Neurospora crassa catalase genes: the Metzenberg RFLP mapping kit applied to an enzyme polymorphism. - J. Simmons; P. Chary; D. O. Natvig (Fungal Genetics Reports, 1987)
Linkage group assignments for two Neurospora crassa catalase genes: the Metzenberg RFLP mapping kit applied to an enzyme polymorphism.